The Development of the United States – China Trade War in 2018 – 2023: An Analysis Through the Theory of Neo-Mercantilism - Muslim, Muhammad Bukhori; Lubis, Flori Mardiani (Peneliti.net, 2024)
ABSTRACT The study entitled: Development of The United States – China Trade War in 2018 –2023: Analtsis Through Neo-Mercantilism Theory, aims to analyze the extent to which the trade war between the United States and China has an impact on the two countries. This research focuses in the form of a question How neo-mercantilism theory analyzes the development of the trade war by the United States and China in 2018-2023? Then, this research uses a literature study with a descriptive method with a qualitative approach. The selection of a qualitative approach is based on the presentation of data in the form of writing and images as a description of the trade war between the United States and China. The descriptive method used in this study is used to identify and analyze the extent to which the trade war between China and the United States has a major war for the economic competition of the two countries and its subsequent effects. Research on the trade war between China and the United States provides a repertoire in international trade in particular and international relations in general. With this study, a further understanding will be obtained and how other countries anticipate and produce solutions to the trade war between the United States and China. Keywords: Trade war, China, United States, Protectionism.